Complexidade na fronteira : estudo do território e do turismo nas cidades de Barracão (PR), Dionísio Cerqueira (SC) e Bernardo de Irigoyen (Arg.) - Fernandes, Rafael Carlos Prieto (2010)
Orientador: Dr. Nilson Cesar Fraga